PEACE SUPPORT OPERATIONS IN SUB-SAHARAN AFRICA: LIVED EXPERIENCES OF EMERGENCY CARE PROVIDERS DURING EXTERNAL DEPLOYMENT - Khoza, Tshikani Lewis; Mshunqane, Nombeko; Sobuwa, Simpiwe (Scientia Militaria - South African Journal of Military Studies, 2020)
Military emergency medical care in support of mission personnel in operational areas serves as a vital element of peace support operations, as it ensures the maintenance of the human resources deployed in mission areas. Although the South African National Defence Force is facing significant financial constraints, it is becoming increasingly mobile, as South Africa continues to pledge military and diplomatic assistance in the African continent to maintain peace and stability, promote development and provide security. Consequently, when deployed abroad, military emergency care providers face unique challenges. The aim of this paper is to describe the lived experiences of Gauteng-based emergency care providers in delivering emergency medical care amid resource constraints during external deployment. The descriptions were extracted from a larger study titled “exploring lived experiences of Gauteng-based military pre-hospital emergency care providers during external deployment”. The research was conducted using a qualitative, exploratory research design and was guided by a phenomenological approach. The findings indicate that Gauteng-based military emergency care providers often did not have enough equipment or appropriate transportation to perform their duties during external deployment. As a result, they are hindered from providing quality care to ill and injured patients.